Validation and psychometric properties of the community assessment inventory in Iranian persons who use drug - Nader Salari; Amir Jalali; Behzad Abdam; Alireza Abdi; Hooman Daryoushi (BMC, 2020)
Abstract Objective Social support is a key factor in the treatment and rehabilitation process of persons who use drug (PWUD). This highlights the need for a valid and reliable tool for assessing social support. The cultural and psychometric properties of community assessment inventory (CAI) in PWUDs under methadone therapy were examined in Iran in 2019. Methods The study was carried out as a validation and methodological study. At first, the original tool was translated into Farsi using forward-backward method. After ensuring face validity and content validity, construct reliability of the tool was supported using explorative and confirmatory factor analysis (EFA & CFA) using a sample group of 392 participants. The participants were selected through convenient-quota sampling from 24 drug clinics. Reliability of the questionnaire was supported using Pearson correlation coefficient and internal consistency based on Cronbach's alpha. Results To determine content validity of the tool, CVI and CVR of it were obtained, which were on average equal to 0.79 and 0.59 respectively. The EFA supported correlation of the 37itmes of the tool (KMO = 0.975, Chi-square = 15,051.6, Pvalue=0.0001). The main indices of the model, based on CFA were higher than 0.9, which support goodness of fit of the model (χ2/DF = 2.98, CFI = 0.91, NFI, TLI = 0.905 GF = 0.92, REMSEA = 0.07, R2 = 0.99). Reliability of the tool based on internal consistency (Cronbach's alpha) for the subscales were in 0.8-0.95 interval and equal to 0.85 for the whole tool. Conclusion As the results showed, CAI had acceptable indices for Iranian PWUDs under methadone therapy. The tool can be used for assessing social support level in the study population. It is a reliable and valid tool for studies in pertinent fields.